(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
The term “Age of Consent” is a term not found in many state statutes, but rather reflects an absence of prohibition. In Indian context, the age of marriage, age for consent to sexual activity and age for procuring a girl for prostitution are different and time and again has lead to peculiar situation posing question not easy to answer. The age of consent for sexual act for girls is different in different circumstances. It is 15 years for a married girl, 16 years for all others and the legal of marriage is 18 years. Observing this peculiar situation, recently the apex court of the country i.e. Supreme Court of India has refereed this matter to Govt. of India to deliberate on the issue and come with suitable amendments in the relevant laws. The Union Government at the centre has constituted a group of ministers (GOM) under the chairmanship of Sh. Arjun Singh Union Minister of Human Resource Development to solve this enigma and suggest necessary amendments. Considering the complexities of the situation, this matter is discussed in the paper.